Content Analysis of Learning Videos on Indonesian Language Material in Elementary Schools on the Rumah Belajar Portal - Dewi, Hestiana; Permana, Rahmat; Hendrawan, Budi (Jurnal Pendidikan Amartha, 2024)
Learning videos are already widely present around us, because they have helped students learn and teach teachers today. Learning video content must be in accordance with the needs of the teaching and learning process. This research was motivated by researchers' concerns about the appropriateness of learning video content in accordance with basic competencies, learning objectives and integrated learning themes, one of which is the presentation of Indonesian language material in elementary schools. The aim of this research is to determine the feasibility of aspects of material composition, presentation structure and language in Indonesian language materials in elementary schools in the construction of learning videos on the Rumah Belajar Portal platform. In this case, the researcher tested the feasibility based on 3 aspects, namely the material composition aspect, the presentation structure aspect and the language aspect of the learning video. The content of elementary school Indonesian language material learning videos needs to be researched because this is to determine the appropriateness of the content for presenting Indonesian language material in elementary schools in learning videos which have contributed to the world of Indonesian education by producing many learning videos. This research uses a content analysis method through a qualitative approach.